A study on relationship between emotional intelligence components of sales managers from Goleman’s viewpoint and sales promotion activities in Iranian business enterprises - Kamal Ghalandari; Soheila Shakoori Yadegari (Management Science Letters)
Winners of the future competition are managers who communicate their human resources in an effective and rewarding way. In this respect, emotional intelligence is an advanced form of focusing on humans in organizational environment and it is a new and suitable instrument for business managers and market theoreticians to direct and satisfy organizational employees and external customers. This paper investigates the relationship between emotional intelligence dimensions and components including self-awareness, self-management, self-motivation, social awareness and relation management and sales promotion activities in Iranian business enterprises. Present research was an applied one with respect to its purpose and a correlational descriptive-survey one with respect to data collection method. Statistical population of the study comprised of 534 managers operating at firms located at West Azarbaijan province in food industry. Among them 225 managers were selected using random sampling procedure based on Krejcie and Morgan’s table. Data on emotional intelligence variable were collected using Goleman’s Emotional Competence Inventory. In addition, sales promotion variable was evaluated using an author-developed questionnaire and reliabilities of these two scales were respectively 0.92 and 0.89. Given the normality of data according to Kolmogorov-Smirnov test, Pearson’s correlation test was used to identify the type of relationship between variables and results suggested a direct significant relationship between all emotional intelligence components including self-awareness, self-management, self- motivation, social awareness and relation management and sales promotion activities at significance level of p ≤0.05.